2003
DOI: 10.1038/sj.gt.3302087
|View full text |Cite
|
Sign up to set email alerts
|

Adeno-associated virus vector-mediated transduction in the cat brain

Abstract: Adeno-associated virus (AAV) vectors are capable of delivering a therapeutic gene to the mouse brain that can result in long-term and widespread protein production. However, the human infant brain is more than 1000 times larger than the mouse brain, which will make the treatment of global neurometabolic disorders in children more difficult. In this study, we evaluated the ability of three AAV serotypes (1,2, and 5) to transduce cells in the cat brain as a model of a large mammalian brain. The human lysosomal e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(69 citation statements)
references
References 43 publications
3
66
0
Order By: Relevance
“…For example, it has been reported that the transduction efficiency of serotype 1 and 5 is superior to AAV2 in the murine brain (29). Studies completed in both rats (6) and cats (30) demonstrated that the transduction efficiency for serotype 1 exceeds both serotypes 2 and 5. Our results support and extend these previous findings.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been reported that the transduction efficiency of serotype 1 and 5 is superior to AAV2 in the murine brain (29). Studies completed in both rats (6) and cats (30) demonstrated that the transduction efficiency for serotype 1 exceeds both serotypes 2 and 5. Our results support and extend these previous findings.…”
Section: Discussionmentioning
confidence: 99%
“…An indication of effi cacy from focal intraparenchymal injections has also been observed in large animal models (e.g., cats and dogs) of various LSDs ( 119,(124)(125)(126)(127). However, despite these encouraging results, scaling this strategy to an infant brain is estimated to nevertheless require between 50 and 350 injection tracts, which is arguably impractical ( 124,127 ).…”
Section: Effi Cacy Of Intracranial Delivery Of Aav Vectors For Neuropmentioning
confidence: 98%
“…In order for such an approach to be clinically effective, it seemed likely that widespread expression in target regions of the brain, cortex, and striatum would be needed. It has been reported that the transduction efficiency in the CNS of AAV1 is superior to that of AAV2 in various animal models, including mouse, rat, and cat (Vite et al, 2003;Wang et al, 2003;Burger et al, 2004). Significantly, however, there is to our knowledge no published report of AAV1 in the primate brain.…”
Section: Introductionmentioning
confidence: 68%
“…A number of reports have shown that the AAV1 serotype transduces the brain more efficiently than does AAV2 (Vite et al, 2003;Wang et al, 2003;Dodge et al, 2005). We have explored in nonhuman primates the utility of this serotype with a vector that encodes a humanized Renilla green fluorescent protein (hrGFP) for which the codon usage has been optimized for use in mammals (see patent WO=2004=005322).…”
Section: Discussionmentioning
confidence: 99%